The Effect of Repairing the Integrity of the Calcaneofibular Ligament During Calcaneal Fracture Surgery on Postoperative Ankle Joint Function - Huang Z; Chen M; Ye Z (Therapeutics and Clinical Risk Management)
Zhenfeng Huang,1,* Mengni Chen,2,* Zhiwei Ye1 1Department of Traumatology and Orthopedics, Wuhan Fourth Hospital, Wuhan, Hubei Province, 430000, People’s Republic of China; 2Department of Operating Room, Tongji Hospital Affiliated to Tongji Medical College of Huazhong University of Science & Technology, Wuhan, Hubei Province, 430030, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zhiwei Ye, Department of Traumatology and Orthopedics, Wuhan Fourth Hospital, 76 Jiefang Avenue, Wuhan City, Hubei Province, 430000, People’s Republic of China, Email gundamiori@163.comBackground: Calcaneal fracture is a common fracture in clinical practice. Open reduction and internal fixation of the calcaneal plate inevitably require cutting or damaging the calcaneofibulartibial fibrous ligament (CFL) beneath the sheath of the fibular muscle tendon. Hence, calcaneal fractures are mainly treated through the lateral L-shaped extension approach. However, there is still controversy over whether the integrity of CFL can be repaired during surgery. Thus, we aimed to explore the effect of repairing CFL during calcaneal fracture surgery on postoperative ankle joint function.Methods: In this retrospective study, we analyzed the clinical data of 84 patients with Sanders type II and III calcaneal fractures admitted to Wuhan Fourth Hospital from March 2021 to May 2023. According to whether CFL was repaired during surgery, the patients were divided into a repair group (n=44) and non-repair group (n=40). These patients underwent surgery by the same surgeon. The perioperative conditions between the two groups were compared. After a one-year follow-up, the rates of excellent ankle function and incidence of complications was also compared.Results: The duration of surgery and hospitalization in the repair group was longer than that in the non-repair group, and the intraoperative blood loss was greater than that in the non-repair group (P< 0.05). After surgery, the excellent and good rate of ankle function in the repair group (90.91%) was higher than that in the non-repair group (67.50%) (P< 0.05). The incidence of complications in the repair group (9.09%) was not significantly higher than that in the non-repair group (7.50%) (P> 0.05).Conclusion: Although preserving CFL integrity during calcaneal fracture surgery increases the duration of surgery and hospitalization, the postoperative recovery of range of motion is good, the rate of excellent ankle function is significantly improved, and there is no significant increase in complications.Keywords: calcaneal fracture, suture anchors, fibular ligament, repair, ankle stability